```
Q, Gamma, omega0 = var( 'Q', 'Gamma', 'omega0')
u = (Q * omega0 + Gamma) / Q
simplify(u)
```

The output is: $$\omega = \frac{Q \omega_0 + \Gamma}{Q}$$

Instead of: $$\omega = \omega_0 + \frac{\Gamma}{Q}$$

1 | initial version |

```
Q, Gamma, omega0 = var( 'Q', 'Gamma', 'omega0')
u = (Q * omega0 + Gamma) / Q
simplify(u)
```

The output is: $$\omega = \frac{Q \omega_0 + \Gamma}{Q}$$

Instead of: $$\omega = \omega_0 + \frac{\Gamma}{Q}$$

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.